PENGARUH PROGRAM KELAS IBU HAMIL TERHADAP PERILAKU IBU MENGENAL TANDA BAHAYA KEHAMILAN, PERSALINAN DAN NIFAS - Yus, Yusnidar; Erawati, Suci; Samura, Dasril (Jurnal Ilmiah Kesehatan Ibu dan Anak, 2023)
One of the causes of death is the complication of pregnancy and childbirth that can arise through danger signs of pregnancy and childbirth. Implementation of The maternal class program aimed to increase maternal knowledge and skills regarding pregnancy, childbirth, family planning, newborn care and pregnancy exercises. Based on reports in 2017, the number of high risk pregnancy among health workers was 701 cases, while the number of high risk pregnancy in Lhokseumawe city community was found to be 39 cases. In Indonesia, the maternal mortality rate was 305 per 100,000 of live birth (Inter-Social Population Survey 2015). The purpose of this research was to find out the effect of the class program of pregnant women on the behavior of mothers to recognize the danger signs of pregnancy, childbirth and puerperium in the work area of ​​Blang Cut Community Health Center in Lhokseumawe in 2019. The type of research was Quasi experiment using one group pre-test and post-test designs with a total sample as many as 73 respondents of pregnant women who took the mother’s class program at the Blang Cut health center in Lhokseumawe City by purposive sampling, data analysis were carried out by univariate and bivariate tests using paired t-test in SPSS version 25 software. The result of this reseach indicated that there was a significant influence on the knowledge factor mother (p = 0,000), maternal attitude factor (p = 0,000), mother’s actions (p = 0,000), recognize the danger signs of pregnancy, childbirth and childbirth. The suggestion that researchers recommend that the Blang Cut Health Center can maintain and improve the quality of class programs for pregnant women to prevent maternal mortality in the work area of ​​Blang Cut Health Center.